KNN-based leadless piezoelectric ceramic material with core-shell structure and preparation method of KNN-based leadless piezoelectric ceramic material
By constructing the core-shell structure of KNN-based lead-free piezoelectric ceramics, and using the reaction epitaxial coating mechanism and solid phase method for control, the problem that the core-shell structure in KNN-based lead-free piezoelectric ceramics is difficult to be highly accurate and reproducible, and the core-shell structure in KNN-based lead-free piezoelectric ceramics is solved, and the core-shell structure is difficult to be prepared with high accuracy and reproducible results are achieved. The high density and excellent electrostrain properties of ceramics are produced.
Patent Information
- Application Number
- CN202310977437.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to achieve high-precision and repeatable preparation of core-shell structures in KNN-based lead-free piezoelectric ceramics, resulting in difficulties in high-performance design and mass production of the material.
The core-shell structure is constructed using the reaction epitaxial coating mechanism. By synthesizing KNLNbCZ and KNLTaCZ powders respectively, and reacting them to form KNLNbTaCZ during the sintering process, the epitaxial coating is applied to the surface of KNLNbCZ to form a core-shell structure ceramic. This method is controlled by solid phase method to ensure the density of the ceramic and the integrity of the core-shell structure.
It realizes the high density and complete core-shell structure of KNN-based lead-free piezoelectric ceramics. It can qualitatively and quantitatively control the relative composition, volume proportion and grain size of the core-shell structure according to design needs, and is suitable for high-performance design and Mass production.
Smart Images

Figure CN119430926A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a KNN-based lead-free piezoelectric ceramic material with a core-shell structure and a preparation method thereof, belonging to the technical field of lead-free piezoelectric ceramic materials. Background Art
[0002] Based on its electromechanical coupling effect, piezoelectric ceramic materials can realize the mutual conversion between electrical energy and mechanical energy, and with its ultra-high precision, ultra-fast response and other characteristics, it is widely used in precision control, piezoelectric drives and other fields. Lead-based piezoelectric ceramics such as lead zirconate titanate (Pb(Zr,Ti)O3, PZT) have long occupied the piezoelectric application market due to their excellent piezoelectric and strain properties, small strain hysteresis and good temperature stability. However, due to the high toxicity of lead oxide (PbO), the PbO content of up to 70% will pose a huge threat to human society and the natural environment during the production, use and disposal of lead-based piezoelectric ceramics. Therefore, the development of high-performance lead-free piezoelectric ceramic materials has become the focus of attention in the industry.
[0003] At present, the perovskite-type lead-free piezoelectric materials that are the focus of attention in the field of piezoelectric ceramics include potassium sodium niobate [(K,Na)NbO3, KNN]-based, bismuth sodium titanate [(Bi 0.5 Na 0.5 )TiO3, BNT] based, and barium titanate (BaTiO3, BT) based systems. Among them, the KNN-based lead-free piezoelectric ceramic system has relatively excellent piezoelectric activity and high local temperature, and is considered to be a very promising lead-free piezoelectric material system. In 2012, Professor Choi's team in South Korea reported a 0.96 (K 0.51 Na 0.47 Li 0.02 )(Nb 0.8 Ta 0.2 )O3-0.04CaZrO3 ceramics (Choi, Si-Young, et al. Gigantic Electrostrain in Duplex Structured Alkaline Niobates. Chemistry of Materials, 2012, 24, 3363-3369), the electro-induced strain is 0.4%, the strain hysteresis is less than 15-20%, and the strain under 1kV / mm "low field" driving conditions is 0.2%, d 33 *As high as 2000pm / V, even much higher than lead-based piezoelectric ceramics. Professor Choi's team analyzed that the interface stress of the core-shell structure in the ceramic can cause the ferroelectric domain in the core to flip reversibly under the action of an external field, thus showing electrostrain performance far higher than that of conventional KNN-based lead-free piezoelectric ceramics. This study provides a design idea of core-shell structure for the research and development of KNN-based lead-free piezoelectric ceramics for pulse drive.
[0004] However, in the following years, there were no related reports that could replicate the work of Professor Choi's team. It was not until 2021 that Professor Li Jingfeng's team at Tsinghua University reported the latest progress on the system (Zhang, Mao-Hua, et al. Enhanced electric-field-induced strains in (K, Na) NbO3 piezoelectrics from heterogeneous structures. Materials Today, 2021, 46, 44-53). It was found that it was very technically difficult to repeat the core-shell structure of the material. In fact, the problem of poor reproducibility in the preparation of the core-shell structure of the KNN-based lead-free piezoelectric ceramic system is not an isolated case. In 2007, Professor Li Jingfeng's team observed a homogeneous core-shell structure formed by abnormal grain growth in pure KNN ceramics and Li / Ta co-doped ceramics (Zhen, Yuhua, et al. Abnormal Grain Growth and New Core–Shell Structure in (K, Na) NbO3-Based Lead-Free Piezoelectric Ceramics. Journal of the American Ceramic Society. 2007, 90, 3496-502). In the same year, Professor Setter's team observed a heterogeneous core-shell structure with Ta-rich shell in a Li / Ta co-doped system with similar composition (Y. Wang, et al., Compositional inhomogeneity in Li-and Ta-modified (K, Na) NbO3 ceramics, Journal of the American Ceramic Society. 2007, 90, 3496-502). Society, 2007, 90, 3485.), the same Li / Ta co-doping showed completely different microstructural states, which indicates that there are still some unknown key factors and process processes affecting the core-shell structure formation of KNN ceramics.
[0005] The above reports reflect that under the existing technical scheme, the process method for constructing a core-shell structure in KNN-based lead-free piezoelectric ceramics is still immature, and it is difficult to achieve high-precision and repeatable preparation of the core-shell structure, which seriously hinders the research and development of high-performance KNN-based lead-free piezoelectric ceramics using the core-shell structure. Summary of the invention
[0006] In view of the above problems, the object of the present invention is to provide a KNN-based lead-free piezoelectric ceramic material with a core-shell structure and a preparation method thereof. The KNN-based lead-free piezoelectric ceramic prepared by this method has high density and complete core-shell structure grains, and can qualitatively and quantitatively control the relative composition, volume proportion, grain size, etc. of the core-shell structure within a large range according to design requirements. Therefore, it can be used as a standard preparation method for high-performance design research and mass production of core-shell structure KNN-based lead-free piezoelectric ceramics.
[0007] In the first aspect, the present invention provides a KNN-based lead-free piezoelectric ceramic material with a core-shell structure, wherein the core is composed of KNLNbCZ, the shell is composed of KNLNbTaCZ generated by the reaction of KNLTaCZ and part of KNLTNbCZ, and the shell layer is epitaxially coated on the surface of the core structure.
[0008] Preferably, the KNN-based lead-free piezoelectric ceramic material with a core-shell structure has a general chemical formula of (1-x)KNLNbCZ-xKNLTaCZ-yLi2O-zMnO2; wherein Li2O and MnO2 are sintering aids and loss inhibitors.
[0009] Preferably, x=0.05-0.4, preferably 0.1-0.25; y=0.005-0.05, preferably 0.01-0.02; z=0.005-0.05, preferably 0.01-0.02.
[0010] Preferably, the chemical formula of KNLNbCZ is (1-e)(K 1-f-g Na f Li g NbO3)-eCaZrO3, wherein e=0-0.1, preferably 0.04; f=0-1, preferably 0.047; g=0-0.06, preferably 0.02;
[0011] Preferably, the chemical formula of KNLTaCZ is (1-m)(K 1-n-o Na n Li o TaO3)-mCaZrO3, wherein m=0~0.1, preferably 0.04; n=0~1, preferably 0.047; o=0~0.06, preferably 0.02.
[0012] Preferably, the average grain diameter of the KNN-based lead-free piezoelectric ceramic is 100 nm to 2 μm, and the average diameter of the core is 40% to 90% of the average size of the core-shell structure grains.
[0013] Preferably, the number ratio of core-shell structure grains to total grains in the KNN-based lead-free piezoelectric ceramic is higher than 95%, and the density is higher than 94%.
[0014] In a second aspect, the present invention provides a method for preparing a KNN-based lead-free piezoelectric ceramic material having a core-shell structure, comprising: (1) mixing KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder to obtain a mixed powder; (2) pressing the mixed powder into a shape to obtain a ceramic green body; (3) Sintering the obtained ceramic green body to obtain the KNN-based lead-free piezoelectric ceramic material with a core-shell structure.
[0015] Preferably, the pressing method is dry pressing and / or cold isostatic pressing; Preferably, the pressure of the dry pressing is 0.5-3 MPa; Preferably, the cold isostatic pressing pressure is 50-300 MPa.
[0016] In a third aspect, the present invention provides a method for preparing a KNN-based lead-free piezoelectric ceramic material having a core-shell structure, comprising: (1) mixing KNLNbCZ powder, KNLTaCZ powder, Li2O powder, MnO2 powder, a solvent, a dispersant, a binder and a plasticizer to obtain a mixed slurry; (2) subjecting the mixed slurry to vacuum degassing, tape casting, lamination / isostatic pressing and cutting to obtain a ceramic green body; (3) Debonding and sintering the obtained ceramic green body to obtain the KNN-based lead-free piezoelectric ceramic material with a core-shell structure.
[0017] Preferably, in step (1), the solid content of the mixed slurry is 45-60wt%; The solvent is selected from at least one of ethanol, ethyl acetate, xylene, butanone and isopropanol, and the added amount is 60-100wt% of the total mass of KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder; The dispersant is selected from at least one of fish oil, castor oil and triolein, and the added amount is 0.5-2wt% of the total mass of KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder; The binder is selected from one of PVB, ethyl cellulose and acrylic resin, and the added amount is 5-20wt% of the total mass of KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder; The plasticizer is selected from at least one of PEG400, PEG200 and BBP, and the added amount is 0.5-5wt% of the total mass of KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder.
[0018] Preferably, in step (1), the mixing method is ball milling; the rotation speed of the ball milling is 200-600 rpm, and the mixing time is 4-48 hours; preferably, the rotation speed of the ball milling is 300-450 rpm, and the mixing time is 8-16 hours.
[0019] Preferably, the debonding temperature is 400-600° C. and the debonding time is 0.5-2 hours.
[0020] Preferably, the average particle size of the KNLNbCZ powder is 100 nm to 1.5 μm; The average particle size of the KNLTaCZ powder is less than 1 / 2 of the average particle size of the KNLNbCZ powder; preferably, the average particle size of the KNLTaCZ powder is 1 / 5 to 1 / 20 of the average particle size of the KKNLNbCZ powder.
[0021] Preferably, the raw material of the Li2O powder is Li2CO3, the average particle size of the Li2CO3 powder is 20nm to 500nm, and the average particle size of the MnO2 powder is 20nm to 500nm.
[0022] Preferably, the sintering temperature is 1180-1220°C, preferably 1200-1220°C; The sintering holding time is no more than 30 minutes, preferably no more than 15 minutes, more preferably 1 to 5 minutes; Preferably, the heating rate of the sintering is 0.5 to 15° C. / min, more preferably 1 to 5° C. / min.
[0023] Preferably, K2CO3, Na2CO3, Li2CO3, CaCO3, ZrO and Nb2O5 are used as raw materials and ball-milled and mixed, and then synthesized and ball-milled again to obtain the KNLNbCZ powder; K2CO3, Na2CO3, Li2CO3, CaCO3, ZrO and Ta2O5 are used as raw materials and mixed by ball milling, and then synthesized, subjected to secondary ball milling treatment and sand milling treatment to obtain the KNLTaCZ powder.
[0024] Furthermore, preferably, the synthesis temperature is 650-1150° C., and the insulation time is 1-5 h; preferably, the synthesis temperature is 800-950° C., and the insulation time is 2-4 h.
[0025] Furthermore, preferably, the speed of the ball milling treatment and the secondary ball milling treatment is 300-500 rpm, and the ball milling time is 4-24 hours; the speed of the sand milling treatment is 1000-4000 rpm, and the time is 0.5-8 hours.
[0026] Beneficial effects of the present invention: 1. The present invention constructs a core-shell structure based on a reaction epitaxial coating mechanism, which changes the existing process technology of mixing all raw materials to prepare pre-synthesized powders. That is, KNLNbCZ and KNLTaCZ powders are synthesized separately, and then the two are further evenly mixed with sintering aids such as Li2CO3 and MnO2 to form a functional composite powder, which provides the best thermal / dynamic initial state for the formation of core-shell structure grains during the sintering process. In this design, KNLNbCZ is used as the main component of the core, which will partially react with KNLTaCZ during the sintering process to generate KNLNbTaCZ and epitaxially coat the surface of KNLNbCZ to construct the expected core-shell structure ceramics. This method makes it easier to realize the construction of the core-shell structure, and also provides a more intuitive design and control method for the preparation of KNN-based core-shell structure ceramics with different elemental compositions, different volume proportions and different grain sizes; 2. As a key technology for controlling the microscopic state of the core-shell structure, the present invention utilizes the characteristic law of densification followed by grain growth during the sintering process of ceramic materials. By performing short-term heat preservation sintering at a temperature far higher than the conventional sintering temperature, the problem of abnormal grain growth caused by the idea of increasing density by extending the heat preservation time in conventional sintering technology is solved. While achieving dense sintering of the ceramic body, the phenomenon of core-shell structure destruction caused by grain growth and annexation is significantly suppressed. This method can ensure the basic configuration of the core-shell structure during the sintering densification process, and provide a solution for the core-shell structure control of the KNN system that is prone to abnormal grain growth; 3. The construction and control method of the core-shell structure ceramics is universal, and is not only applicable to the preparation of KNN-based core-shell structure ceramics with different element compositions, different volume proportions, and different grain sizes, but can also be used for the preparation of BNT-based and BT-based lead-free piezoelectric ceramics with core-shell structures; 4. The core-shell structure ceramics are prepared by the traditional solid phase method, which does not require special equipment. The preparation process meets the many requirements of material research and development and mass production for process simplicity, operability and repeatability, and has great economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1The XRD patterns of the ceramics obtained in Examples 1-7 and their partial magnifications near 46°; Figure 2 The XRD patterns of the ceramics obtained in Comparative Examples 1-6 and their local magnified images at around 46°; Figure 3 Surface SEM images of ceramics prepared for the main examples; Figure 4 SEM images of polished sections of ceramics obtained for the main examples; Figure 5 The surface SEM images and polished cross-section SEM images of the ceramics obtained in the main comparative examples; Figure 6 The dielectric thermograms of the ceramics obtained in Examples 2-7; Figure 7 The dielectric thermograms of the ceramics obtained in Comparative Examples 1-6; Figure 8 The hysteresis loop and biaxial strain curve of the ceramic obtained in Example 6; Fig. 9 The uniaxial strain curve of the ceramic obtained in Example 6; Fig.10 The hysteresis loop and biaxial strain curve of the ceramic obtained for Comparative Example 5; Fig.11 This is the uniaxial strain curve of the ceramic obtained in Comparative Example 5. DETAILED DESCRIPTION
[0028] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0029] In the present disclosure, the KNN-based lead-free piezoelectric ceramic material with a core-shell structure has Nb-rich KNLNbCZ as the main component of the core, which partially reacts with Ta-rich KNLTaCZ to form a shell layer, Li2O plays a role in sintering, and MnO2 has both the role of sintering and reducing dielectric loss. Among them, the distribution of K, Na, Li, Ca, and Zr in the lead-free piezoelectric ceramic is uniform, the content of Nb in the core layer is higher than that in the shell layer, and Ta is only distributed in the shell layer.
[0030] In an optional embodiment, the chemical formula of the KNN-based lead-free piezoelectric ceramic material having a core-shell structure is: 0.8[0.96(K 0.51 Na 0.47 Li 0.02 NbO3)-0.04CaZrO3]-0.2[0.96(K 0.51 Na 0.47 Li 0.02TaO3)-0.04CaZrO3]-0.01Li2O-0.02MnO2, abbreviated as 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2.
[0031] In an optional embodiment, the KNN-based lead-free piezoelectric ceramic material with a core-shell structure has a high density (>94%) and complete core-shell structure grains, with an average grain size between 800 and 870 nm and a standard deviation of less than 250 nm.
[0032] In order to solve the problem that the existing technical methods are difficult to achieve repeatable preparation and precise control of the KNN ceramic core-shell structure, the present invention uses a solid phase method to overcome the above technical difficulties. The following is an exemplary description of the preparation method of the KNN-based lead-free piezoelectric ceramic material with a core-shell structure.
[0033] According to 0.96 (K 0.51 Na 0.47 Li 0.02 NbO3)-0.04CaZrO3 and 0.96(K 0.51 Na 0.47 Li 0.02 The stoichiometric ratios of K, Na, Li, Ca, Zr, Nb, Ta and other elements in KNLNbCZ-0.04CaZrO3 are determined, and the raw materials corresponding to KNLNbCZ and KNLTaCZ are weighed: K2CO3, Na2CO3, Li2CO3, CaCO3, ZrO, Nb2O5 and Ta2O5. The raw materials are mixed evenly to form mixed slurries for preparing KNLNbCZ and KNLTaCZ, respectively, and then the mixed slurries are dried, ground and sieved to obtain mixed raw powders.
[0034] The mixed raw powders corresponding to KNLNbCZ and KNLTaCZ are pre-fired and kept warm for 1 to 5 hours at 650 to 1150°C, then cooled to room temperature with the furnace, and dried, ground and sieved by secondary ball milling / sand milling to obtain KNLNbCZ and KNLTaCZ pre-synthesized powders. Preferably, the pre-fired temperature is 800-950°C, and the pre-fired insulation time is 2-4 hours. Among them, the ball milling speed is 300 to 500 rpm, and the ball milling time is 4 to 24 hours. Moreover, after ball milling, the KNLTaCZ pre-synthesized powder is further sand milled at a speed of 1000 to 4000 rpm for 0.5 to 8 hours. The final average particle size of the obtained KNLTaCZ powder is less than 1 / 2 of the average particle size of the KNLNbCZ powder, preferably 1 / 5 to 1 / 10.
[0035] According to the composition ratio of the chemical potential 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2, KNLNbCZ, KNLTaCZ, Li2CO3, MnO2 are weighed, and solvents, dispersants, binders, and plasticizers are added. After ball milling for 4 to 48 hours, the mixture is evenly mixed and then cast to obtain a green porcelain thick film, and then the ceramic body is obtained after cutting, laminating, isostatic pressing, and cutting. The speed of ball milling mixing is 200 to 600 rpm, and the mixing time is 4 to 48 hours. Preferably, the speed of ball milling mixing is 300 to 450 rpm, and the ball milling mixing time is 8 to 16 hours.
[0036] The powder molding process can also adopt the traditional dry pressing molding process, that is, the inorganic powder is ball-milled and mixed evenly without adding dispersants, binders, plasticizers, etc., and then dried and ground, a binder is added to granulate and sieve, and then an appropriate amount of powder is loaded into the mold and pressurized to form a dense green body.
[0037] The ceramic body is kept at 350-650°C (preferably 400-500°C) for 0.5-2h to remove organic components, and is heated to 1100-1240°C at a rate of 0.1-10°C / min, kept for 0-20min, and then cooled to room temperature with the furnace to obtain 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramics with high density and complete core-shell structure.
[0038] In an optional embodiment, the sintering temperature is 1180-1220°C, preferably 1200-1220°C. If the sintering temperature is too high, the porcelain will show signs of melting. If the sintering temperature is too low, the density of the porcelain will be difficult to reach an ideal state. The sintering heating rate is 0.5-15°C / min, preferably 1-5°C / min. The sintering holding time is 0-30min, preferably 0-15min, and more preferably 1-5min. If the sintering time is too long, abnormal grain growth will occur.
[0039] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0040] Example 1 (1) K2CO3, Na2CO3, Li2CO3, CaCO3, ZrO, Nb2O5 and Ta2O5 were used as raw materials, respectively, at 0.96 (K 0.51 Na 0.47 Li 0.02 NbO3)-0.04CaZrO3 (i.e. KNLNbCZ) and 0.96 (K 0.51 Na 0.47 Li 0.02 The raw materials are weighed in the stoichiometric ratio of K, Na, Li, Ca, Zr, Nb, Ta and other elements in 0.04CaZrO3 (i.e., KNLTaCZ), and then put into a ball mill and add appropriate amount of ethanol and zirconium oxide ball milling beads, and ball mill them at a speed of 400 rpm on a planetary ball mill for 12 hours. After being fully mixed, the mixed raw materials are placed in an oven and dried at 100°C for 12 hours; (2) After drying, the KNLNbCZ raw material powder and the KNLTaCZ raw material powder were placed in an alumina crucible, and the crucible was placed in a muffle furnace and heated to 900° C. at a heating rate of 5° C. / min, and kept warm for 2 hours to react and synthesize KNLNbCZ ceramic powder and KNLTaCZ ceramic powder; (3) Grind the synthesized KNLNbCZ ceramic powder and KNLTaCZ ceramic powder respectively and put them into a ball mill, add an appropriate amount of ethanol, and perform secondary ball milling on a planetary ball mill at a speed of 400 rpm for 12 hours. Among them, after the secondary ball milling, the ball milling beads of KNLTaCZ are filtered out and moved into a sand mill, and further ground at a speed of 2800 rpm to reduce the particle size. After the grinding is completed, the mixed slurry is placed in an oven and dried at 100°C for 12 hours. After drying, the powder is ground and passed through a 200-mesh sieve; (4) According to the chemical formula 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2, 44.055 g KNLNbCZ, 16.423 g KNLTaCZ, 0.239 g Li2CO3 and 0.556 g MnO2 were weighed and loaded into a ball mill. Then, appropriate amounts of ethylene glycol, butanone, triolein, acrylic resin, BBP, PEG400, etc. were weighed and loaded into the ball mill. The mixture was mixed at a speed of 250 rpm for 16 hours. (5) After being fully mixed, the ball mill beads in the slurry are filtered out, and a square sheet green body of 8.5 mm × 8.5 mm × 0.7 mm is prepared after degassing, casting, cutting, lamination, isostatic pressing, hot cutting and other processes; (6) A certain amount of green bodies were placed on a zirconia setter, and the setter was placed in a muffle furnace and heated to 450°C at a rate of 3°C / min, and kept at this temperature for 2 hours to remove organic components in the green bodies. Then, the temperature was further increased to 1120°C at a rate of 2°C / min and kept at this temperature for 1 minute to obtain a 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet.
[0041] Example 2 It is basically the same as Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1140°C.
[0042] Example 3 It is basically the same as Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1160°C.
[0043] Example 4 It is basically the same as Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1180°C.
[0044] Example 5 It is basically the same as Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1200°C.
[0045] Example 6 It is basically the same as Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1220°C.
[0046] Example 7 It is basically the same as Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1240°C.
[0047] Example 8 It is basically the same as Example 4, except that the sintering heating rate of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 0.5°C / min.
[0048] Example 9 It is basically the same as Example 4, except that the sintering heating rate of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1°C / min.
[0049] Example 10 It is basically the same as Example 4, except that the sintering heating rate of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 4°C / min.
[0050] Embodiment 11 It is basically the same as Example 4, except that the sintering heating rate of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 8°C / min.
[0051] Example 12 It is basically the same as Example 11, except that the sintering holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 2 minutes.
[0052] Embodiment 13 It is basically the same as Example 11, except that the sintering holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 4 minutes.
[0053] Embodiment 14 It is basically the same as Example 11, except that the sintering and holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 8 minutes.
[0054] Embodiment 15 It is basically the same as Example 11, except that the sintering and holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 16 minutes.
[0055] Example 16 It is basically the same as Example 4, except that the sintering holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 4 minutes.
[0056] Embodiment 17 It is basically the same as Example 4, except that the sintering and holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 16 minutes.
[0057] Embodiment 18 It is basically the same as Example 4, except that the sintering and holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 30 minutes.
[0058] Embodiment 19 It is basically the same as Example 4, except that the chemical formula is 0.85KNLNbCZ-0.15KNLTaCZ-0.01Li2O-0.02MnO2. The reduction in the amount of KNLTaCZ can reduce the relative content of Ta in the core-shell ceramic shell layer, thereby regulating the phase structure, dielectric properties and stress state of the core and shell in the core-shell structure.
[0059] Embodiment 20 It is basically the same as Example 4, except that the chemical formula is 0.90KNLNbCZ-0.10KNLTaCZ-0.01Li2O-0.02MnO2, and the sintering temperature is 1160° C. The reduction in the amount of KNLTaCZ can further reduce the relative content of Ta in the shell layer of the core-shell ceramic structure, thereby regulating the phase structure, dielectric properties and stress state of the core and shell in the core-shell structure.
[0060] Embodiment 21 It is basically the same as Example 4, except that the chemical formula is 0.8KNLNbCZ-0.2KNLTaCZ-0.02Li2O-0.01MnO2. A small adjustment in the amount of Li2O and MnO2 will not significantly affect the core-shell structure state and performance parameters of the KNN-based lead-free piezoelectric ceramic.
[0061] Comparative Example 1 (1) K2CO3, Na2CO3, Li2CO3, CaCO3, ZrO, Nb2O5 and Ta2O5 were used as raw materials, respectively, at 0.96 (K 0.51 Na 0.47 Li 0.02 NbO3)-0.04CaZrO3 (i.e. KNLNbCZ) and 0.96 (K 0.51 Na 0.47 Li 0.02 The raw materials are weighed in the stoichiometric ratio of K, Na, Li, Ca, Zr, Nb, Ta and other elements in 0.04CaZrO3 (i.e., KNLTaCZ), and then put into a ball mill and add appropriate amount of ethanol and zirconium oxide ball milling beads, and ball mill them at a speed of 400 rpm on a planetary ball mill for 12 hours. After being fully mixed, the mixed raw materials are placed in an oven and dried at 100°C for 12 hours; (2) After drying, the KNLNbCZ raw material powder and the KNLTaCZ raw material powder were placed in an alumina crucible, and the crucible was placed in a muffle furnace and heated to 900° C. at a heating rate of 5° C. / min, and kept warm for 2 hours to react and synthesize KNLNbCZ ceramic powder and KNLTaCZ ceramic powder; (3) Grind the synthesized KNLNbCZ ceramic powder and KNLTaCZ ceramic powder respectively and put them into a ball mill, add an appropriate amount of ethanol, and perform secondary ball milling on a planetary ball mill at a speed of 400 rpm for 12 hours. Among them, after the secondary ball milling, the ball milling beads of KNLTaCZ are filtered out and moved into a sand mill, and further ground at a speed of 2800 rpm to reduce the particle size. After the grinding is completed, the mixed slurry is placed in an oven and dried at 100°C for 12 hours. After drying, the powder is ground and passed through a 200-mesh sieve; (4) According to the chemical formula 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2, 44.055 g KNLNbCZ, 16.423 g KNLTaCZ, 0.239 g Li2CO3 and 0.556 g MnO2 were weighed and loaded into a ball mill. Then, appropriate amounts of ethylene glycol, butanone, triolein, acrylic resin, BBP, PEG400, etc. were weighed and loaded into the ball mill. The mixture was mixed at a speed of 250 rpm for 16 hours. (5) After being fully mixed, the ball mill beads in the slurry are filtered out, and a square sheet green body of 8.5 mm × 8.5 mm × 0.7 mm is prepared after degassing, casting, cutting, lamination, isostatic pressing, hot cutting and other processes; (6) A certain amount of green bodies were placed on a zirconia setter, and the setter was placed in a muffle furnace and heated to 450°C at a rate of 3°C / min, and kept at this temperature for 2 hours to remove organic components in the green bodies. Then, the temperature was further increased to 1070°C at a rate of 2°C / min and kept at this temperature for 120 minutes to obtain a 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet.
[0062] Comparative Example 2 It is basically the same as Comparative Example 2, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1080°C.
[0063] Comparative Example 3 It is basically the same as Comparative Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1090°C.
[0064] Comparative Example 4 It is basically the same as Comparative Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1100°C.
[0065] Comparative Example 5 It is basically the same as Comparative Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1110°C.
[0066] Comparative Example 6 It is basically the same as Comparative Example 1, except that the sintering temperature of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 1120°C.
[0067] Comparative Example 7 It is basically the same as Example 4, except that the sintering and holding time of the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet is 60 minutes.
[0068] Comparative Example 8 It is basically the same as Example 4, except that the chemical formula is 0.95KNLNbCZ-0.05KNLTaCZ-0.01Li2O-0.02MnO2, and the sintering temperature is 1160°C.
[0069] Comparative Example 9 It is basically the same as Example 4, except that the chemical formula is KNLNbCZ-0.01Li2O-0.02MnO2 and the sintering temperature is 1120°C.
[0070] Comparative Example 10 It is basically the same as Example 4, except that the chemical formula is 0.8KNLNbCZ-0.2KNLTaCZ.
[0071] Performance Test: The density of ceramic pieces was tested using the drainage method; XRD, SEM and other methods were used to characterize the structure and microstructure of the ceramic sheet. Before the test, the 0.8KNLNbCZ-0.2KNLTaCZ-0.01Li2O-0.02MnO2 ceramic sheet was ground to a certain thickness with sandpaper of 6-30μm particle size, and then preliminarily polished with 6μm, 3μm, and 1μm polishing pastes, and finally vibrated polished with 50nm Al2O3 suspension. The dielectric temperature spectrum of the prepared samples was tested by an impedance analyzer to reflect the phase change law. The hysteresis loops and uniaxial and biaxial strain curves of the prepared samples were tested using a ferroelectric analyzer.
[0072] As attached Figure 1 The XRD spectra of the main examples are shown in the figure. It can be seen from the figure that the main phase of the piezoelectric ceramic prepared by the present invention is a perovskite structure. As the sintering temperature gradually increases from 1120°C to 1240°C, the relative intensity of the 002 and 200 diffraction peaks of Examples 1-7 does not change significantly, indicating that the method described in the present invention can suppress the phase structure change caused by the increase in sintering temperature. Figure 2 As shown, as the sintering temperature gradually increases from 1070°C to 1120°C, the relative intensities of the 002 and 200 diffraction peaks of Comparative Examples 1-6 change significantly, indicating that the use of traditional long-term heat preservation sintering will lead to significant changes in the phase structure.
[0073] As attached Figure 3 and attached Figure 4 The following are the surface and polished surface SEM micro-region morphology images of the main embodiments. In each embodiment, the proportion of core-shell structure grains is close to 100%, and the grain size has not changed significantly. The size proportion of the core layer and the shell layer in the grain is relatively consistent, and the average diameter of the core is 40% to 50% of the average grain diameter. Figure 5 As shown, with the increase of sintering temperature, the abnormal growth of grains began to appear in Comparative Example 2, the thickness of the shell layer increased, and it developed rapidly in Comparative Examples 3-6. The abnormal growth of grains was accompanied by the mutual annexation of grains, resulting in a serious imbalance in the ratio of the average diameter of the core to the average diameter of the grains. The ratio between the average diameter of the core and the evaluated grain size dropped from about 56% to below 20%, and the ratio was even lower than 5% to 10% in the abnormally grown grains. In addition, when the amount of KNLTaCZ was less than 10%, although the proportion of core-shell structure grains to the total grains was still around 100%, the difficulty of controlling the abnormal growth of grains increased, and the ratio of the average diameter of the core to the average diameter of the grains in the abnormally grown grains was lower than 5% to 10%. When the amount of KNLTaCZ was 0, there were no more core-shell structure grains. The sample preparation conditions, sintering shrinkage, density, grain size and core-shell structure state data of the above embodiments and comparative examples are summarized as shown in Table 1 below.
[0074] Table 1 Sample preparation conditions, sintering shrinkage, density, grain size and core-shell structure state of the embodiments and comparative examples:
[0075] As attached Figure 6As shown in the figure, all the examples show the unique double peak characteristics of core-shell structure ceramics. The peak near 210°C is the Curie phase transition of the core, and the peak at 50-100°C is the Curie phase transition of the shell. Thanks to the relatively stable phase composition and core-shell structure state, the dielectric temperature spectra of Examples 2-7 show similar characteristics. Figure 7 As shown, as the sintering temperature increases, the dielectric temperature spectra of Comparative Examples 1-6 are significantly different, and the phase transition temperature moves significantly. Considering the dependence between the performance of piezoelectric ceramics and the phase transition temperature, it can be determined that the preparation of the KNN ceramics using the sintering system of Comparative Examples 1-6 has problems such as sintering temperature sensitivity and poor repeatability. In addition, since no loss inhibitor is added, the dielectric loss of Comparative Example 10 is greater than 50%.
[0076] As attached Figure 8 and attached Fig. 9 The hysteresis loop, biaxial strain curve and uniaxial strain curve of Example 6 are shown. The coercive field can be determined to be 0.97 kV / mm and the saturation polarization intensity is 17.5 μC / cm through the hysteresis loop. 2 , the residual polarization intensity is 8.1μC / cm 2 The larger difference between the saturation polarization intensity and the remnant polarization intensity reflects the spontaneous reversal characteristics of the ferroelectric domain under the core-shell structure, which helps to improve its electrostrain performance. Figure 7 The biaxial strain shows symmetric characteristics, with a positive strain of 0.28% and no negative strain. Figure 8 The strain of the uniaxial strain is 0.24%, and the strain hysteresis is 14%, which shows that Example 6 has excellent electrostrain performance. Fig.10 and attached Fig.11 The hysteresis loop, biaxial strain curve and uniaxial strain curve of comparative example 5 are shown. Fig.10 The hysteresis loop confirms that its coercive field is 1.98 kV / mm, which is much larger than that of Example 6, indicating that it requires a higher electric field to drive. In addition, its saturation polarization intensity is 17.5 μC / cm 2 , the residual polarization intensity is 13μC / cm 2 , the difference between the two is significantly smaller than that of Example 6, indicating that the spontaneous reversal of its ferroelectric domain is not as significant as that of Example 6. The weak spontaneous reversal of ferroelectric domains makes the electrostrain performance of Comparative Example 5 significantly worse than that of Example 6. The maximum strain of its biaxial strain curve is 0.15%, and there is negative strain, while the maximum strain of the uniaxial strain curve is only 0.11%. In summary, Example 6 has a more reasonable core-shell size ratio, so its comprehensive performance is significantly better than that of Comparative Example 5, which shows that strictly controlling the morphology of the core-shell structure is extremely important for obtaining excellent electrostrain performance.
Claims
1. A KNN-based lead-free piezoelectric ceramic material with a core-shell structure, characterized in that: The core is composed of KNLNbCZ, the shell is composed of KNLNbTaCZ generated by the reaction of KNLTaCZ and part of KNLTNbCZ, and the shell layer is epitaxially coated on the surface of the core structure.
2. The KNN-based lead-free piezoelectric ceramic material with a core-shell structure according to claim 1, characterized in that: The chemical formula of the KNN-based lead-free piezoelectric ceramic material with a core-shell structure is (1-x)KNLNbCZ-xKNLTaCZ-yLi2O-zMnO2; Wherein x = 0.05 to 0.4, preferably 0.1 to 0.25; y = 0.005 to 0.05, preferably 0.01 to 0.02; z=0.005 to 0.05, preferably 0.01 to 0.
02.
3. The KNN-based lead-free piezoelectric ceramic material with a core-shell structure according to claim 1 or 2, characterized in that: The chemical formula of KNLNbCZ is (1-e)(K 1-f-g Na f Li g NbO3)-eCaZrO3; wherein e=0-0.1, preferably 0.04; f=0-1, preferably 0.047; g=0-0.06, preferably 0.02; The chemical formula of KNLTaCZ is (1-m)(K 1-n-o Na n Li o TaO3)-mCaZrO3; wherein m = 0 to 0.1, preferably 0.04; n = 0 to 1, preferably 0.047; o = 0 to 0.06, preferably 0.02; The Li2O is a sintering aid, and the MnO2 is a dielectric loss inhibitor.
4. The KNN-based lead-free piezoelectric ceramic material with a core-shell structure according to any one of claims 1 to 3, characterized in that: The average size of the core-shell structure grains of the KNN-based lead-free piezoelectric ceramic material with a core-shell structure is 100nm-2μm, and the average diameter of the core is 40%-90% of the average size of the core-shell structure grains.
5. The KNN-based lead-free piezoelectric ceramic material with a core-shell structure according to any one of claims 1 to 4, characterized in that: In the KNN-based lead-free piezoelectric ceramic material with a core-shell structure, the proportion of core-shell structure grains to total grains is higher than 95%.
6. A method for preparing a KNN-based lead-free piezoelectric ceramic material with a core-shell structure as claimed in any one of claims 1 to 5, characterized in that: include: (1) mixing KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder to obtain a mixed powder; (2) pressing the mixed powder into a shape to obtain a ceramic green body; (3) Sintering the obtained ceramic green body to obtain the KNN-based lead-free piezoelectric ceramic material.
7. The preparation method according to claim 6, characterized in that: The pressing method is dry pressing and / or cold isostatic pressing; preferably, the pressure of the dry pressing is 0.5 to 5 MPa; preferably, the pressure of the cold isostatic pressing is 10 to 300 MPa.
8. A method for preparing a KNN-based lead-free piezoelectric ceramic material as claimed in any one of claims 1 to 5, characterized in that: include: (1) mixing KNLNbCZ powder, KNLTaCZ powder, Li2O powder, MnO2 powder, a solvent, a dispersant, a binder and a plasticizer to obtain a mixed slurry; (2) subjecting the mixed slurry to vacuum degassing, tape casting, lamination / isostatic pressing and cutting to obtain a ceramic green body; (3) Debonding and sintering the obtained ceramic green body to obtain the KNN-based lead-free piezoelectric ceramic material.
9. The preparation method according to claim 8, characterized in that: In step (1), the solid content of the mixed slurry is 45-60wt%; the solvent is selected from at least one of ethanol, ethyl acetate, xylene, butanone and isopropanol, and the added amount is 60-100wt% of the total mass of the KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder; the dispersant is selected from at least one of fish oil, castor oil and triolein, and the added amount is 0.5-2wt% of the total mass of the KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder; The binder is selected from one of PVB, ethyl cellulose and acrylic resin, and the added amount is 5-20wt% of the total mass of KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder; The plasticizer is selected from at least one of PEG400, PEG200 and BBP, and the added amount is 0.5-5wt% of the total mass of KNLNbCZ powder, KNLTaCZ powder, Li2O powder and MnO2 powder.
10. The preparation method according to claim 8, characterized in that: In step (3): the debonding temperature is 400-600° C. and the debonding time is 1-2 hours.
11. The preparation method according to claim 6 or 8, characterized in that: In step (1), the mixing method is ball milling; the rotation speed of the ball milling is 200-600 rpm, and the mixing time is 4-48 hours; preferably, the rotation speed of the ball milling is 300-450 rpm, and the mixing time is 8-16 hours.
12. The preparation method according to claim 6 or 8, characterized in that: In step (1), the average particle size of the KNLNbCZ powder is 100 nm to 1.5 μm; The average particle size of the KNLTaCZ powder is less than 1 / 2 of the average particle size of the KNLNbCZ powder; preferably, the average particle size of the KNLTaCZ powder is 1 / 5 to 1 / 20 of the average particle size of the KNLNbCZ powder.
13. The preparation method according to claim 6 or 8, characterized in that: In step (1), the average particle size of the Li2O powder is 20nm to 500nm; the average particle size of the MnO2 powder is 20nm to 500nm.
14. The preparation method according to claim 6 or 8, characterized in that: In step (3), the sintering temperature is 1180-1220° C., preferably 1200-1220° C.; The sintering holding time is no more than 30 minutes, preferably no more than 15 minutes, more preferably 1 to 5 minutes; Preferably, the heating rate of the sintering is 0.5 to 15° C. / min, more preferably 1 to 5° C. / min.
15. The preparation method according to claim 6 or 8, characterized in that: K2CO3, Na2CO3, Li2CO3, CaCO3, ZrO and Nb2O5 are used as raw materials and ball-milled and mixed, and then synthesized and subjected to secondary ball-milling treatment to obtain the KNLNbCZ powder; K2CO3, Na2CO3, Li2CO3, CaCO3, ZrO and Ta2O5 are used as raw materials and mixed by ball milling, and then synthesized, subjected to secondary ball milling treatment and sand milling treatment to obtain the KNLTaCZ powder.
16. The preparation method according to claim 15, characterized in that: The synthesis temperature is 650-1150° C., and the insulation time is 1-5 hours; preferably, the synthesis temperature is 800-950° C., and the insulation time is 2-4 hours.
17. The preparation method according to claim 15, characterized in that: The speed of the ball milling and secondary ball milling treatment is 300-500 rpm, and the ball milling time is 4-24 hours; the speed of the sand milling treatment is 1000-4000 rpm, and the time is 0.5-8 hours.
Citation Information
Patent Citations
Wide sintering temperature region and wide ingredient regulation lead-free piezoelectric texture ceramic and preparation method thereof
CN107098699A
Calcium zirconate and tantalum doped potassium sodium niobate-based piezoelectric ceramic and preparation method and application thereof
CN111072385A
Piezoelectric ceramics for piezoelectric element, contain crystal grain comprising shell and core phases, each differing in composition and having preset amount of crystal lattice defects
DE102010000783A1
Piezoelectric ceramics, and laminated piezoelectric ceramic component
JP2013014470A
Dielectric ceramic composition and electronic device
US20060088709A1